2011
DOI: 10.1007/s10509-011-0910-8
|View full text |Cite
|
Sign up to set email alerts
|

Bianchi type-I cosmological models for binary mixture of perfect fluid and dark energy

Abstract: We consider a self consistent system of Bianchi Type-I cosmology and Binary Mixture of perfect fluid and dark energy. The perfect fluid is taken to be obeying equations of state p P F = γρ P F with γ ∈ [0, 1]. The dark energy is considered to be obeying a quintessence-like equation of state where the dark energy obeys equation of state 0]. Exact solutions to the corresponding Einstein field equations are obtained. Some special cases are discussed and studied. Further more power law models and exponential model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…There are many radically different models for DE to fit the current observations such as quintessence, phantom, tachyon, chaplygin gas. In recent years, many authors [2][3][4][5][6][7][8][9][10][11][12][13][14][15] have shown keen interests in studying the DE universe with various contexts. However, the simplest and most theoretically appealing candidate for .…”
Section: Introductionmentioning
confidence: 99%
“…There are many radically different models for DE to fit the current observations such as quintessence, phantom, tachyon, chaplygin gas. In recent years, many authors [2][3][4][5][6][7][8][9][10][11][12][13][14][15] have shown keen interests in studying the DE universe with various contexts. However, the simplest and most theoretically appealing candidate for .…”
Section: Introductionmentioning
confidence: 99%
“…where p and  are the pressure and energy density of DE and  is an EoS parameter which is useful to describe cosmic acceleration. A number of authors [7][8][9][10][11][12][13][14][15] have studied binary mixture of perfect fluid (PF) and anisotropic DE for Bianchi type-I, II, III, V, VI0, plane symmetric, kaluza-klein as well as higher dimensional cosmological models too. Recently, the anisotropic dark energy has been studied for Bianchi type-IX space-time [16].…”
Section:   Pmentioning
confidence: 99%